Dr. Indira Goswami : in search of modernity - Gagai, Hr̥daẏānanda. (Delhi : B.R. Pub. Corp., 2010)
Study on the works of Māmaṇi Raẏachama Goswāmī, b. 1942, Assamese author.
Includes bibliographical references (p. 268-269).
"Bibliography of Indira Goswami": (p. [255]-260).
Keywords: Goswāmī, Māmaṇi Raẏachama, -- 1942-2011 -- Criticism and interpretation; Goswāmī, Māmaṇi Raẏachama, -- 1942-2011.; Criticism, interpretation, etc